Efficacy of two entomopathogenic nematodes strains Steinernema siamkayai and S. abbasi against the 3rd instar larvae of Chiloloba acuta - Pokhrel, M; Thapa, RB; Gharty Chhetry, YD; Sporleder, M (Journal of Agriculture and Environment, 2018)
Larvae of scarabaeid beetle Chiloloba acuta (Coleoptera: Cetoninae) was found high densities in Khulekhani VDC, Makawanpur district. These insects are major pest of flower. The efficacy of two species of entomopathogenic nematodes, Steinernema siamkayai (CD1) and S. abbasi (CS1) was tested against third instar of Chiloloba acuta. In a dose response experiments, 0, 125, 250, 500, 1000, 2000 and 4000 infective juveniles (IJs) were inoculated in 50 ml plastic vial containing 40g silt loam soil (45.3% sand, 33.5% silt, 12.2% clay 4.913 organic matter and 5.5pH) and a single C. acuta larva. Mortality of C. acuta exposed to series of increase dose of two nematodes strains was analysed two days intervals upto 14th days after the inoculation by time dose mortality regression. Between these strains, S. abbasi found more effective (LD50 44.9IJs/ml) as compared to S. siamkayai (LD50 98.1IJ/ml) after 14th days. At initial days both strains had high LD50 value and it was gradually decreased with increase time.